AB0138 INCREASED CD38 EXPRESSION LEVELS ON IMMUNE CELL SUBSETS IN SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Ostendorf, L.; Enghard, P.; Durek, P.; Heinrich, F.; Mashreghi, M. F.; Burmester, G. R.; Radbruch, A.; Hiepe, F.; Alexander, T.
Abstract : Background: Plasma Cells (PCs) are implicated in the pathogenesis of Systemic Lupus erythematosus (SLE) and their targeting proved a promising treatment modality. As there is a monoclonal therapeutic antibody targeting CD38 licensed for clinical use in multiple myeloma, plasma cell depletion via CD38 seems to represent a promising path in SLE treatment. While CD38 Is highly expressed on plasmacells, it is present on the surface of subsets of T and B lymphocytes as well as myeloid cells. Objectives: Here we aim to identify the differential expression of CD38 on peripheral blood leukocytes in SLE compared to healthy controls (HC) investigate the function of CD38+ T lymphocytes Methods: We performed flow cytometry to investigate the expression of CD38 on peripheral blood mononuclear cells of SLE patients (n=36) and HCs (n=20). We additionally analyzed the expression of T lymphocytes within the urine of patients with lupus nephritis as well as the skin of SLE patients. We investigated the inflammatory potential of CD38 positive memory T lymphocytes after stimulation and performed single-cell RNA sequencing analyses. Results: CD38 Expression is increased on certain immune cell subsets: Plasmablasts and unswitched Memory B cells, as well as plasmacytoid dendritic cells and CD16+ non-classical monocytes. We observed a drastic increase CD38 in both memory CD4 and CD8 T lymphocytes in SLE patients. These cells were mostly effector T cells (and not regulatory T cells) and expressed other markers of T cell activation and proliferation. We found an enrichment of CD38+ memory T cells in the urine of patients with lupus nephritis. After polyclonal stimulation of T cells, CD38+ produced less inflammatory cytokines. Preliminary single-cell sequencing results indicate that CD38+ CD8+ T-lymphocytes have decreased clonal diversity and that these cells express genes associated with exhaustion and type 1 interferon response. Conclusion: Increased CD38 expression on various lymphocyte subsets provides an additional rationale for investigating CD38-directed therapies in SLE. Targeting CD38 could not only deplete plasma cells but also has the potential to target interferon alpha producing plasmacytoid dendritic cells and modulate inflammatory T cell functions. Disclosure of Interests: Lennard Ostendorf: None declared, Philipp Enghard: None declared, Pawel Durek: None declared, Frederik Heinrich: None declared, Mir-Farzin Mashreghi: None declared, Gerd Rüdiger Burmester Consultant of: AbbVie Inc, Eli Lilly, Gilead, Janssen, Merck, Roche, Pfizer, and UCB Pharma, Speakers bureau: AbbVie Inc, Eli Lilly, Gilead, Janssen, Merck, Roche, Pfizer, and UCB Pharma, Andreas Radbruch: None declared, Falk Hiepe: None declared, Tobias Alexander: None declared